Seroprevalencia de Brucella spp. en poblaciones de équidos(equidaes) en la zona sur de la Provincia de Los Ríos - Palacios Bajaña, Cindy Mariam (2023)
Brucellosis is an infection caused by a facultative intracellular bacterium belonging to the Brucella spp. This has come to be considered one of the most important zoonoses in the world due to its implications on public health and its repercussions on livestock production. As mentioned above, this work was carried out with the purpose of determining the seroprevalence of Brucella spp in equine populations in the southern area of the Province of Los Ríos. Therefore, in this investigation, 364 equids belonging to the southern area of the province mentioned above were sampled in the following cantons (Baba, Vinces, Palenque and Babahoyo), which will be 44 farms or properties. The positive cases of Brucella spp were evaluated using the non-parametric test for a single sample, chi square test, the positive cases were 17, which represents 5%. It should be noted that the positive cases occurred mostly in the Baba canton with 16 cases, which represents 94.12%, while in the Babahoyo canton only 1 case occurred, 6 horses, 5 foals, 3 mares and 3 fillies. Among the animals most susceptible to brucella spp are horses.